Path Analysis of Knowledge, Education Level, Income and Behavior to Hypertension Incidence in Semarang City - Novia Ika Pratiwi; Oktia Woro Kasmini Handayani; Intan Zainafree (Universitas Negeri Semarang, 2026)
Globally 33% of the population aged 30-70 years will suffer from hypertension in 202. This study uses a quantitative approach with a cross-sectional study design. The research sample of 400 respondents used the consecutive sampling technique. Data collection was conducted using questionnaire instruments and medical record data. The samples taken were respondents aged >15 years who took blood pressure measurements at the Telogosari Kulon, Telogosari Wetan and Kedungmundu Health Centers. Data analysis using chi-square test and logistic regression with SPSS and path analysis using JASP. Most of the respondents in this study were female, elderly, and had high education levels, low knowledge, and bad behavior. The results of the study stated that statistically there was a direct influence of education level (p-value =<0.001), income (p-value =<0.001) and lifestyle behavior (p-value =<0.001) on the incidence of hypertension. Statistically, there is an indirect influence of knowledge (p-value=<0.001), education level (p-value=0.001), income (p value =<0.001) through lifestyle behaviors on the incidence of hypertension in Semarang City. Variables of knowledge about hypertension (p-value=0.772) has no direct effect on the incidence of hypertension. Lifestyle behavior has the greatest effect (25%) in influencing the incidence of hypertension in Semarang City. The conclusion of this study is that there is a direct influence of education, income and lifestyle on the incidence of hypertension, and there is an indirect influence between knowledge, education level, and income through behavior on the incidence of hypertension in Semarang City.Suggestions for agencies and the community to increase preventive efforts, especially lifestyle behavior.